2017
DOI: 10.18632/oncotarget.21452
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of anti-VEGF agents in the treatment of elderly hepatocellular carcinoma: a systematic review

Abstract: PurposeWe aimed to investigate the role of anti-vascular endothelial growth factor (VEGF) agents, including tyrosine-kinase inhibitors or monoclonal anti-bodies, in the treatment of elderly hepatocellular carcinoma (HCC) patients.Materials and MethodsDatabases from PubMed, Web of Science and abstracts presented at ASCO meeting up to March 31, 2017 were searched to identify relevant studies. The endpoints were overall survival (OS) and progression-free survival (PFS). Data were examined using age cutoffs of 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…VEGF levels in HCC patients are higher than in patients with chronic hepatitis and cirrhosis. The increase of VEGF is negatively correlated with the prognosis of liver cancer [87,88] . The current only FDA approved first line therapeutic drug for advanced HCC, sorafenib, is also a tyrosine kinase inhibitor (TKI) directed against the VEGF family.…”
Section: Vegf Pathwaymentioning
confidence: 99%
“…VEGF levels in HCC patients are higher than in patients with chronic hepatitis and cirrhosis. The increase of VEGF is negatively correlated with the prognosis of liver cancer [87,88] . The current only FDA approved first line therapeutic drug for advanced HCC, sorafenib, is also a tyrosine kinase inhibitor (TKI) directed against the VEGF family.…”
Section: Vegf Pathwaymentioning
confidence: 99%
“…As the dominant clinically available targeting reagents for HCC, sorafenib and regorafenib, acting on Raf/mitogen-activated protein kinase/extracellular signal-regulated kinase (RAF/MEK/ERK) and VEGF signaling pathways, did not result in remarkable improvement in the patient's outcome as other targeting reagents did in breast cancer or lung cancer [11][12][13]. The accumulating clinical and biological databases of cancer disease provide reliable source to dig out and verify new clues for cancer diagnosis and treatment [14].…”
Section: Introductionmentioning
confidence: 99%
“…2 With the advent of molecularly targeted therapeutic agents (MTAs), the treatment of HCC has substantially improved. 3 In March 2018, lenvatinib (LEN), an MTA, was approved for the treatment of unresectable HCC following sorafenib and regorafenib treatment, as the first-line treatment for patients with unresectable HCC in the United States of America, the European Union, Japan, and China, based on the results of the REFLECT trial, a global multicenter randomized phase 3 trial of LEN for HCC. [4][5][6][7] It has been reported that treatment with LEN results in a decrease in tumor blood flow during the early stages of administration.…”
Section: Introductionmentioning
confidence: 99%
“… 2 With the advent of molecularly targeted therapeutic agents (MTAs), the treatment of HCC has substantially improved. 3 …”
Section: Introductionmentioning
confidence: 99%